Changing Landscape of Liver Cancer in California: A Glimpse Into the Future of Liver Cancer in the United States. (13th December 2018) - Han, Summer S; Kelly, Scott P; Li, Yuqing; Yang, Baiyu; Nguyen, Mindie; So, Samuel; Rosenberg, Philip S; Hsing, Ann W
Abstract: Background: Asians and Hispanics currently have the highest incidence rates of hepatocellular carcinoma (HCC) in the United States. The numbers of these minority populations are rapidly increasing, reshaping the demographic in the United States and particularly California, where approximately one-third of US Asians and Hispanics reside. With the changing demographic and rising incidence of HCC that has tripled during the past three decades, it is important to forecast the future burden of HCC by age, sex, and race/ethnicity to plan prevention and control strategies for HCC. Methods: We used four Surveillance, Epidemiology, and End Results Program registries to obtain incidence data for California during 2000 to 2013, and 14 registries to represent non-California states. We applied age-period-cohort models to estimate future HCC incidence rates, and estimated HCC burden by multiplying incidence forecasts by corresponding US Census population projections. Results: Our forecasts for California suggest that in 2030 Hispanics and blacks will have the highest HCC incidence rates and Asians the lowest. While incidence among whites, blacks, and Hispanics in California increased successively for each birth year cohort from 1915 through 1955, incidence among Asians in California decreased for each successive birth year cohort from 1915 through 1975. In contrast, consistent declines were not seen among Asians in the rest of the United States. In California, the estimated burden of HCC is 6482 new cases in 2030, where 80.0% of these patients are older than 65 years (vs 44.5% in 2014). The relative increase of burden in 2030 vs 2014 for this 65 years and older age group is especially high among Hispanics (318.3%), whereas it is the lowest among Asians (53.2%) in California. Conclusions: Prevention efforts in California should target persons currently ages 50 to 64 years who will make up the older age group (>65 years) in 2030, especially among Hispanics with the most rapid increase of HCC burden through 2030.